IOT-BASED SMART KITCHENS: ENHANCING MEAL PREPARATION AND NUTRITION MONITORING THROUGH INTELLIGENT SYSTEMS (International Journal of Food and Nutritional Sciences, 2021)
Abstract: The integration of Internet of Things (IoT) technology into kitchen environments is revolutionizing meal preparation and nutrition monitoring. This research paper explores the impact of IoT-based smart kitchens in enhancing cooking experiences and promoting healthier eating habits. By leveraging interconnected devices such as smart appliances, sensors, and AI-driven systems, IoT-enabled kitchens offer personalized meal recommendations, automate cooking processes, and provide real-time feedback on nutritional intake. These intelligent systems not only improve efficiency but also support dietary management by tracking and analyzing users' eating habits. The numerous benefits, challenges such as data privacy concerns, cybersecurity risks, and the complexity of device integration persist. This paper discusses these challenges and potential solutions while also exploring emerging trends in the field, such as advancements in machine learning and predictive analytics that could further transform smart kitchens. The study concludes by highlighting the future potential of IoT-based smart kitchens to reshape culinary practices and improve overall health and well-being, emphasizing the need for continued innovation and addressing existing limitations.